2022
DOI: 10.3389/fimmu.2022.853891
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Complement 3 and Complement 4 Are Promising Biomarkers for Distinguishing NMOSD From MOGAD and Are Associated With the Blood-Brain-Barrier Disruption in NMOSD

Abstract: Background and ObjectiveNeuromyelitis optica spectrum disorders (NMOSD) and myelin oligodendrocyte glycoprotein antibody (MOG-IgG) associated disease (MOGAD) are autoimmune inflammatory demyelinating diseases of the central nervous system (CNS). As the clinical features of NMOSD are similar to MOGAD, diagnostic confusion exists between the two diseases. To better discriminate NMOSD from MOGAD, we investigated whether the plasma levels of complement 3 (C3) and complement 4 (C4) are different in NMOSD and MOGAD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 38 publications
1
10
0
Order By: Relevance
“…Liu et al. found that C3 levels in the blood plasma were positively correlated with CSF WCC ( 23 ). In the MOGAD group, C3 consumption was lower, while CSF WCC were higher ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Liu et al. found that C3 levels in the blood plasma were positively correlated with CSF WCC ( 23 ). In the MOGAD group, C3 consumption was lower, while CSF WCC were higher ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…found that C3 levels in the blood plasma were positively correlated with CSF WCC ( 23 ). In the MOGAD group, C3 consumption was lower, while CSF WCC were higher ( 23 ). This indirectly supports the earlier idea that the majority of MOG-IgG detected in the CSF is synthesized intrathecally by plasmablasts inside the CSF, whereas most of the AQP4-IgG in the CSF originated from extrathecal sources and passively entered the CSF through the blood-brain barrier ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence, for example, supports a complement and coagulation protein pathway mechanism by which omega-3 polyunsaturated fatty acids might contribute to cognitive and symptom improvements in individuals with early psychosis [41]. A role for C4 in neuroinflammation is based on positive, negative, and mixed associations of C4 levels with markers of white matter integrity, CSF biochemistry, cortical thinning, and patterns of expression with postmortem brain structures and functions [31,32,42,51,52,54,[90][91][92][93][94][95][96][97].…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenic effects of AQP4‐IgG binding to astrocytes are primarily thought to activate complement‐dependent cytotoxicity via the classical pathway by binding to C1q, which is followed by C3 convertase enzymes converting C3 into C3a and C3b 30,31 . This process will cause subtle consumption of C3, and multiple studies have found that an obvious declined serum/plasma level of C3 in patients with NMOSD, especially AQP4‐IgG (+) NMOSD than healthy controls 32,33 . In the attack phase, AQP4‐IgG initiates a more severe attack on astrocytes, leading to the activation of the complement system and a massive depletion of C3, which may explain why patients in the acute phase have significantly lower levels of C3 compared to the remission phase.…”
Section: Discussionmentioning
confidence: 99%
“… 30 , 31 This process will cause subtle consumption of C3, and multiple studies have found that an obvious declined serum/plasma level of C3 in patients with NMOSD, especially AQP4‐IgG (+) NMOSD than healthy controls. 32 , 33 In the attack phase, AQP4‐IgG initiates a more severe attack on astrocytes, leading to the activation of the complement system and a massive depletion of C3, which may explain why patients in the acute phase have significantly lower levels of C3 compared to the remission phase. However, plasma C4 levels did not differ significantly between patients in the attack and remission phases in this study, similar to the results of a related study in SLE, which showed that C3 level was associated with disease activity and lupus nephritis, but C4 level was not.…”
Section: Discussionmentioning
confidence: 99%